Al-Ṭarīqah wa al-ḥarakah al-iḥtijājīyah al-ijtimā‘īyah bi Jawa fī al-qarn al-tāsi‘ ‘ashar: Al-Shaykh Aḥmad al-Rifā‘ī Kalisalak Namūdhajan - Islam, M. Adib Misbachul (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2016)
This article delves into a manuscript of Nazam Tarekat written by Kiai Ahmad ar-Rifai Kalisalak. So far, there has been no study related to Kiai Ahmad ar-Rifai Kalisalak which used Nazam Tarekat as the primary source. The research on this manuscript and its social context highlights the special nature of Kiai Ahmad ar-Rifai’s teachings on Sufism, such as his attitude toward Javanese traditional leaders who have abandoned morality. The other special feature of his teachings on Sufism is that they show the determination of alim adil based on fiqh as the qualification for Sufi teachers. The analysis of this alim adil concept as the qualification for Sufi teachers, put into the dynamics of socio-religious movements in 19th century Java, reveals that besides being a qualification for teachers of Sufism, alim adil also became the ideology for the social protest movement against Dutch colonialization in Java. The strength of the fiqh factor in the concept of alim adil indicates that Kiai Ahmad ar-Rifai Kalisalak’s movement was far from messianic-millenarianism.DOI: 10.15408/sdi.v23i3.3716